1987
DOI: 10.1523/jneurosci.07-10-03282.1987
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory interactions between spiking and nonspiking local interneurons in the locust

Abstract: Simultaneous intracellular recordings were made from pairs of spiking and nonspiking local interneurons in the metathoracic ganglion of the locust to search for interactions that might underlie tactile and proprioceptive reflexes of a leg. A spike in a spiking local interneuron is followed after a consistent latency (0.6 +/- 0.12 msec, mean +/- SD) by an IPSP in a particular nonspiking interneuron. The connection appears to be direct and chemically mediated. By contrast, manipulating the membrane potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…Although cells are classified into two groups based on the ability to fire either one or trains of APs, there is heterogeneity within these groups based on AP duration, amplitude, and fir-ing frequency. The range of firing patterns in our study is similar to those previously reported for the cytochalasin B-treated giant neurons (Saito and Wu, 1991) as well as responses recorded in situ from Drosophilu (Ikeda and Kaplan, 1970) and from other insect preparations (Ikeda and Kaplan, 1970;Goodman and Heitler, 1979;Burrows, 1987;Christensen et al, 1988;Laurent, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…Although cells are classified into two groups based on the ability to fire either one or trains of APs, there is heterogeneity within these groups based on AP duration, amplitude, and fir-ing frequency. The range of firing patterns in our study is similar to those previously reported for the cytochalasin B-treated giant neurons (Saito and Wu, 1991) as well as responses recorded in situ from Drosophilu (Ikeda and Kaplan, 1970) and from other insect preparations (Ikeda and Kaplan, 1970;Goodman and Heitler, 1979;Burrows, 1987;Christensen et al, 1988;Laurent, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…Previous work has revealed the numbers and identities for most of the key components responsible for the generation of movement as well as the feedback loops necessary to maintain its adaptiveness (Berkowitz and Laurent 1996;Bräunig 1985;Bräunig and Eder 1998;Burrows 1982Burrows , 1987aBurrows ,b, 1988Burrows and Pflüger 1986;Field and Burrows 1982). Spiking local interneurons play an important role in reflex loops controlling the leg by integrating sensory information from the chordotonal organ and other sensory receptors and synapsing onto nonspiking local interneurons (Burrows 1987a), projection interneurons (Laurent 1987), and motor neurons (Burrows 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The population of sensory neurons of the FeCO has an overlapping range of responses from encoding position to velocity and to acceleration (Kondoh et al 1995) and is responsible for a resistance reflex that opposes the movement applied to the leg (Field and Burrows 1982). In locusts, in common with other insects, the FeCO afferents synapse directly onto spiking and nonspiking local interneurons and leg motor neurons (Burrows 1987a;Büschges 1989). Different sensory neurons respond to different qualities and ranges of stimuli (Kondoh et al 1995), and these properties are thought to be translated onto their principal postsynaptic targets, the spiking local interneurons (Burrows 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It can be predicted that, in invertebrates at least, local or unisegmental interneurons serve not only to mediate local reflexes (Burrows and Siegler, 1982) and to shape motor outputs (Burrows, 1987b), but, in addition, to sharpen the receptive fields of intersegmental interneurons. What is now needed is to understand how the specific signals transmitted by intersegmental interneurons interact with distant local centers.…”
Section: Role Of the Inhibitionmentioning
confidence: 99%
“…Since no mechanosensory neuron is known to make inhibitory connections in the central nervous system of insects, at least one layer of interneurons must be interposed between the afferents and the intersegmental interneurons. Spiking local intemeurons in a population that mediates reflex inhibition of motor neurons (Burrows and Siegler, 1982) and of nonspiking local interneurons (Burrows, 1987b) are the intercalated interneurons (Laurent, 1987~).…”
mentioning
confidence: 99%